Socialization Understood in a Dynamic Way - Todorović, Milorad V. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
In psychology, the process of socialization often gets the meaning it does not actually have and it also gets attached to things that are related to other processes. Here, socialization is understood only as the entering of a subject into a socio-symbolic order where he acquires his own identity. This entering into a separating order places the good on one side and the bad on the other, whilte it is essentially a process that strongly designates the world by giving a man's instinctive nature the social contours obtained through imposed standards. Every form of anti-social behavior, as well as every great psychological deviation, shows the lack of proper integration into the symbolic. Psychology, as a general theory of the psyche, and social psychology especially, indicates the social and cultural conditions that influence the mental construction. Without the dynamics of psychology, which depicts the psychological life through mental dynamics, psychological etiologies especially of those forms of behavior that have no social verification would be neglected. Starting from the social and cultural conditions that build the 'psychological', it explains how the motives for suppression of all impulsive tendencies, such as aggression and libido, are built. Mastering the impulses involves the construction of a moral instance (super-ego) that differentiates and exists as a constant threat to the ego who tries to smuggle certain instinctive tendencies. Given that it is known, ever since Freud, that – from the standpoint of limiting the impulses, from the standpoint of morality – a man has a completely immoral part (instinctive, id); a part that is struggling to be moral (ego); and a super-ego that can be hyper-moral, and then become utterly cruel (Freud 2006a: 120), it can be observed that socialization is involved in both good and bad part of a man. Success in a man's defense from Eros and Thanatos, on the one hand, and in his defense from the impulses of one and the other, on the other hand, will determine the forms of behavior dominated by aggression, violence, crime, incest, and many other forms of perversion and neurosis.
Keywords: Name of the Father; dynamic psychology; origin of the subject; integration into the symbolic; suppression of impulses; socialization